Effect of transition metals (Zr and Hf) on microstructure, thermodynamic parameters, electrical resistivity, and magnetization of CuAlMn-based shape memory alloy - Kok, Mediha; Qadir, Razaw Abdalla; Mohammed, Safar Saeed; Qader, Ibrahim Nazem (Springer Heidelberg, 2021)
In the present study, the effect of adding different compositions of Zirconium and Hafnium on thermal, electrical, and magnetization behaviors of a Cu-Al-Mn-based shape memory alloy has been investigated. The samples were produced by the arc melting method in a controlled environment. According to DSC results, the austenite phase transformation temperatures were decreased by adding Zr and Hf, while the martensite phase transformation temperatures were increased, consequently, the temperature hysteresis was narrowed. Likewise, the same results were obtained in the electrical resistivity measurement. On the other hand, the enthalpy change in both heating and cooling cycles was increased. The XRD analysis presented that all specimens have approximately the same pattern with martensite phase formed in two different morphologies (beta'(1) and gamma'(1)), and the same result was investigated in SEM analysis. Also, the crystallite size was reduced by the effect of Zr and Hf. The magnetization behavior of the alloys revealed that the ternary Cu70Al24Mn6 (atomic percent) alloy has a superparamagnetic behavior at room temperature, but when Hf and/or Zr were added, the alloy changed to a paramagnetic shape memory alloy, indicating that Hf and Zr could fully shift the L2(1) phase to the DO3 phase, which can effect on the magnetic behavior of the alloys.
Keywords: Transformation Temperatures